Characterization of the chromobindins. Soluble proteins that bind to the chromaffin granule membrane in the presence of Ca2+. - Carl E. Creutz; Lisa Dowling; Julianne J. Sando; C. Villar‐Palasi; Judith H. Whipple; William J. Zaks (1983)
EGTA, ethylene glycol bis(P-aminoethyl ether)-N,N,N',N'-tetraacetic acid